(untitled) (Biological Sciences - PJSIR, 2011)
This study describes an effective and reproducible protocol for the mass multiplication of marigold (Tagetes erecta L.) for commercial purpose. Twenty five different combinations of BAP, IAA, GA3 and AgNO3 were added to the basal MS medium to culture marigold explants. The highest mean number (4.83±0.49) and length (5.28 cm ±1.06) of healthy shoots per explant was observed in media supplemented with 2 mg/L BAP along with 2 mg/L IAA. When these shoots were sub-cultured for root development, the maximum number (17.08±2.44) and length (13.67 cm ±0.98) of roots were produced in media supplemented with 4mg/L BAP and 2 mg/L IAA. Addition of gibberellic acid and AgNO3 did not have any significant effect on shoot proliferation and root development of marigold.